The effects of detraining and training on adipose tissue lipid droplet in obese mice after chronic high-fat diet. Issue 1 (December 2017) - Bae, Ju; Woo, Jinhee; Roh, Hee; Lee, Yul; Ko, Kangeun; Kang, Sunghwun; Shin, Ki
Abstract Background It is well known that exercise promotes lipolysis by stimulating the lipid droplet (LD) signaling pathway. However, few studies have been conducted to examine the effect of detraining with high fat diet (HFD) and training effects after long-term HFD. Here, we investigated the effect of detraining and training on adipose tissue LD pathway in diet-induced obese mice after continuous HFD. Methods Seventy male C57BL/6 mice were randomly assigned into a Normal diet + Sedentary group (ND, n = 10) or a High-fat diet + Sedentary group (HF, n = 50); in the HF group, obesity was induced by a 45% fat chow for six weeks. For the subsequent eight weeks, the HF group was randomly subdivided into an HF (n = 30) or an HF + training group (HFT, n = 20), and the HFT group was subjected to treadmill training while on an HFD. Following this eight-week period, the HFT group stopped exercising (HFT-DT group, n = 10), and the mice in the HF group were randomly subdivided into an HF (n = 10) or an HF + training group (HF-T, n = 10). After training and detraining, abdominal visceral fat was obtained and analyzed by histological staining and western blot. Results Treadmill exercise decreased body weight and fat mass (P <0.05), and increased the levels of PKA, perilipin1, CGI-58, ATGL, and HSL (P <0.05) after eight weeks of training. Following eight weeks of detraining, the levels of PKA and HSL were decreased (P <0.05); however, exercise after chronic HFD increased the levels of PKA, perilipin1, CGI-58, ATGL, and HSL (P <0.05), and decreased body weight and fat mass (P <0.05). Conclusions Regardless of dietary restrictions, exercise is an effective treatment for obesity, owing to the regulation of LD signaling proteins. Moreover, the effects of regular exercise after chronic HFD were similar to those of exercise in the absence of HFD. Therefore, although obesity is induced by chronic HFD, exercise without dietary change is sufficiently effective for obesity treatment regardless of the preceding HFD period.